SAT0640-HPR RHEUMATOLOGY CARE OF MIGRANTS FROM SUB-SAHARAN AFRICA; A QUALITATIVE PILOT STUDY OF PATIENTS' PERSPECTIVES. (2nd June 2020) - Rutter-Locher, Z.; Galloway, J.; Lempp, H.
Abstract : Background: Rheumatological diseases are common in Sub-Saharan Africa [1] but specialist healthcare is limited and there are less than 150 rheumatologists currently serving 1 billion people in Sub-Saharan Africa [2]. Rheumatologists practising in the UK NHS are likely to be exposed to migrant patients. There is therefore, an unmet need for health care providers to understand the differences in rheumatology healthcare provision between Sub-Saharan Africa and the UK and the barriers which migrants face in their transition of rheumatology care. Objectives: To gain an understanding of the experiences of patients with rheumatological conditions, about their past healthcare in Sub-Saharan Africa and their transition of care to the UK. Methods: A qualitative study using semi-structured interviews was conducted. Participants were recruited from two rheumatology outpatient clinics in London. Thematic analysis was applied to identify key themes. Results: Seven participants were recruited. Five had rheumatoid arthritis, one had ankylosing spondylitis and one had undifferentiated inflammatory arthritis. Participants described the significant impact their rheumatological conditions had on their physical and emotional wellbeing, including their social and financial implications. Compared to the UK, rheumatology healthcare in Sub-Saharan Africa was characterised by higher costs, limited access to specialists, lack of investigations and treatments, the use of traditional medicines and poor communication by clinicians. Barriers to transition of rheumatology care to the UK were: poor understanding of rheumatological conditions by the public and primary care providers, lack of understanding of NHS entitlements by migrants, fear of data sharing with immigration services and delayed referral to specialist care. Patient, doctor and public education were identified by participants as important ways to improve access to healthcare. Conclusion: This study has described, for the first time, patients' perspectives of rheumatology health care in Sub-Saharan Africa and the transition of their care to the UK. These initial findings allow healthcare providers in the UK to tailor management for this migrant population and suggests that migrants need more information about their NHS entitlements and specific explanations on what non-clinical data will be shared with immigration services. To increase access to appropriate care, a concerted effort by clinicians and public health authorities is necessary to raise awareness and provide better education to patients and migrant populations about rheumatological conditions. References: [1]G. Mody, "Rheumatology in Africa-challenges and opportunities, " Arthritis Res. Ther., vol. 19, no. 1, p. 49, 2017. [2]M. A. M. Elagib et al., "Sudan and Sweden Active Rheumatoid Arthritis in Central Africa: A Comparative Study Between, " J. Rheumatol. J. Rheumatol. January, vol. 43, no. 10, pp. 1777–1786, 2016. Acknowledgments: We are grateful to the patients involved in this study for their time and involvement. Disclosure of Interests: None declared